The Impacts of Uncertainty Stress on Mental Disorders of Chinese College Students: Evidence From a Nationwide Study - Wu, Dan; Yu, Lingwei; Yang, Tingzhong; Cottrell, Randall; Peng, Sihui; Guo, Wei; Jiang, Shuhan (Frontiers in Psychology, 2020)
Objectives This study aimed to examine the relationships between types of stress and students’ mental health, to distinguish the effects of stressors on mental health problems, and to explore the important role of uncertainty stress on the development of mental disorders in a nationally representative sample of Chinese college students. Methods A cross-sectional multi-stage study was conducted. Participants were 11,954 students, who were recruited from 50 Chinese universities located in 43 cities covering 23 provinces, autonomous regions and municipalities across China. Student Daily Stress Questionnaire (SDSQ) was applied to measure the different types of stress and mental health status was measured using the 12-item Chinese Health Questionnaire (CHQ). Both unadjusted and adjusted logistic regression models were utilized in the statistical analyses. Multilevel analyses were performed to examine the variation of mental disorder at both the individual- and university-level. Results The prevalence of mental disorders was 22.8% (95% CI: 22.0%-23.5%). The unadjusted models showed that age, gender, grade, major, and university location and type were the correlates of mental disorders among students. The unadjusted models developed in this research found that study stress, life stress, and uncertainty stress were positively associated with mental disorder. The multilevel logistic regression models showed that uncertainty stress was far more likely to result in students’ mental disorders than study or life stress after controlling for university level. The greater the perceived uncertainty stress, the higher the prevalence of mental disorders. Conclusions This study provides robust evidence of the impact of uncertainty stress on mental disorders among college students. Compared with life and study stress, more attention should be given to uncertainty stress. The information from this study should be helpful when considering effective mental health policies and interventions among college students in China.